Structural Features of Ion Transport and Allosteric Regulation in Sodium-Calcium Exchanger (NCX) Proteins - Giladi, Moshe; Tal, Inbal; Khananshvili, Daniel (Frontiers in Physiology, 2016)
Na+/Ca2+ exchanger (NCX) proteins extrude Ca2+ from the cell to maintain cellular homeostasis. Since NCX proteins contribute to numerous physiological and pathophysiological events, their pharmacological targeting has been desired for a long time. This intervention remains challenging owing to our poor understanding of the underlying structure-dynamic mechanisms. Recent structural studies have shed light on the structure-function relationships underlying the ion-transport and allosteric regulation of NCX. The crystal structure of an archaeal NCX (NCX_Mj) along with molecular dynamic simulations and ion flux analyses, have assigned the ion binding sites for 3Na+ and 1Ca2+, which are being transported in separate steps. In contrast with NCX_Mj, eukaryotic NCXs contain the regulatory Ca2+-binding domains, CBD1 and CBD2, which affect the membrane embedded ion-transport domains over a distance of 80 Å. The Ca2+-dependent regulation is ortholog, isoform and splice-variant dependent to meet physiological requirements, exhibiting either a positive, negative or no response to regulatory Ca2+. The crystal structures of the two-domain (CBD12) tandem have revealed a common mechanism involving a Ca2+-driven tethering of CBDs in diverse NCX variants. However, dissociation kinetics of occluded Ca2+ (entrapped at the two-domain interface) depends on the alternative-splicing segment (at CBD2), thereby representing splicing-dependent dynamic coupling of CBDs. The HDX-MS, SAXS, NMR, FRET, equilibrium 45Ca2+ binding and stopped-flow techniques provided insights into the dynamic mechanisms of CBDs. Ca2+ binding to CBD1 results in a population shift, where more constraint conformational states become highly populated without global conformational changes in the alignment of CBDs. This mechanism is common among NCXs. Recent HDX-MS studies have demonstrated that the apo CBD1 and CBD2 are stabilized by interacting with each other, while Ca2+ binding to CBD1 rigidifies local backbone segments of CBD2, but not of CBD1. The extent and strength of Ca2+-dependent rigidification at CBD2 is splice-variant dependent, showing clear correlations with phenotypes of matching NCX variants. Therefore, diverse NCX variants share a common mechanism for the initial decoding of the regulatory signal upon Ca2+ binding at the interface of CBDs, whereas the allosteric message is shaped by CBD2, the dynamic features of which are dictated by the splicing segment.